A super-tough medium-entropy alloy and a preparation method thereof
Patent Information
- Application Number
- CN202410265022.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-08
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2044-03-08
AI Technical Summary
Existing medium-entropy alloys cannot achieve both high strength and toughness in the extreme low-temperature environment of 4.2K, and therefore cannot meet the service performance requirements of high-end cryogenic equipment such as liquid engine components for aerospace rockets.
A medium-entropy alloy with a specific elemental composition is used to induce the precipitation of nano-L12 precipitates through solution heat treatment, cold rolling deformation, and aging heat treatment, forming a fine-grained structure. This achieves lattice strengthening, solution strengthening, and precipitation strengthening, thereby improving the alloy's ultra-low temperature mechanical properties.
At 4.2K, the medium-entropy alloy exhibits a yield strength of 1500-2200MPa, a tensile strength of 2000-2500MPa, and a fracture strain of 7-30%, demonstrating excellent cryogenic strength and toughness, which meets the material requirements of high-end cryogenic equipment.
Smart Images

Figure BDA0004732065270000061
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alloys, specifically relating to an ultra-strong and tough medium-entropy alloy and its preparation method. Background Technology
[0002] High-end cryogenic equipment includes fuel tanks and valves for pressurization and delivery systems in liquid rocket engines, requiring structural materials to possess both extremely high strength and toughness at ultra-low temperatures. For example, the key components of modern high-thrust-ratio liquid rocket engines operate at temperatures ranging from -183°C to -253°C, necessitating materials with exceptionally high strength and toughness at these ultra-low temperatures. These performance characteristics directly determine the thrust of the liquid rocket engine.
[0003] High-entropy and medium-entropy alloys strengthened by nano-L12 phase (ordered intermetallic compound) precipitation exhibit excellent plasticity and mechanical strength matching at ultra-low temperatures, far exceeding those of currently used 1Cr18Ni9Ti, 304, and 316 stainless steel, and are expected to meet the actual needs of liquid engine components for aerospace rockets. For example, the medium-entropy alloy disclosed in patent document CN115927944 A possesses both good tensile plasticity and strength at an ultra-low temperature of 77K (-196℃). However, the strength and toughness of this type of alloy material at -269℃ are still unclear. As the operating temperature further decreases, the lattice resistance of the alloy increases significantly, which may reduce the toughness while enhancing the strength of the alloy material. This means that it may not be able to maintain high strength and toughness simultaneously in lower operating environments, thus failing to meet the performance requirements for service at even lower temperatures.
[0004] Currently, there is limited research on the properties of alloy materials for cryogenic applications, especially in extreme low-temperature environments such as 4.2K (-269℃). In particular, research on the impact of preparation processes on the properties of alloys suitable for cryogenic environments needs further improvement in order to obtain better strength and toughness and meet the urgent needs of high-performance cryogenic structural materials for aerospace rocket liquid engine components or other fields. Summary of the Invention
[0005] To address the problem that existing medium-entropy alloys cannot maintain their toughness in extreme low-temperature environments of 4.2K (-269℃), this invention provides an ultra-tough medium-entropy alloy and its preparation method, which is designed for ultra-low temperature applications.
[0006] To achieve the above objectives, the following technical solutions are specifically included:
[0007] A method for preparing a medium-entropy alloy includes the following steps:
[0008] (1) Clean the raw materials of elemental metals Co, Cr, Ni, Al, Ti, V and Ta respectively, and then make them according to the chemical formula (NiCoCr) based on the percentage of metal atoms. 73 V2Ta(Ni6AlTi)3 is prepared by weighing the various elemental metals and performing vacuum melting. After melting, the molten alloy is cast to obtain (NiCoCr). 73 V2Ta(Ni6AlTi)3 alloy ingot;
[0009] (2) (NiCoCr) 73 The V2Ta(Ni6AlTi)3 alloy ingot is subjected to solution heat treatment, cold rolling deformation, and aging heat treatment in sequence to obtain the medium entropy alloy; the aging heat treatment temperature is 700-1000℃.
[0010] In the method of this invention, (NiCoCr) 73 The medium-entropy alloy is obtained by sequentially subjecting V2Ta(Ni6AlTi)3 alloy ingots to solution heat treatment, cold rolling deformation, and aging heat treatment. This invention, by selecting specific alloying elements and combining them with appropriate solution heat treatment, cold rolling deformation, and aging heat treatment, can fully utilize the effects of lattice strengthening, solution strengthening, precipitation strengthening, and grain refinement strengthening, as well as the back stress strengthening effect generated by heterogeneous grain structure. This achieves the goal of simultaneously increasing the strength and toughness of the medium-entropy alloy at ultra-low temperatures. The specific mechanism is analyzed as follows:
[0011] (1) After aging heat treatment, the precipitation of nano-L12 precipitates in the alloy can be induced. Both the nano-L12 phase and the alloy matrix are face-centered cubic structures. The nano-L12 phase and the matrix alloy are coherent and have excellent precipitation strengthening effect. At the same time, the precipitate can also prevent grain coarsening, making the grains finer and improving the mechanical strength of the medium-entropy alloy. In addition, the low stacking energy of the NiCoCr matrix (lower than that of the high-entropy alloy NiCoCrFe) makes it easy for the medium-entropy alloy to form stacking faults and deformation twins during ultra-low temperature deformation, ensuring good toughness.
[0012] (2) In the alloy of the present invention, V and Ta elements are dissolved in the medium-entropy alloy matrix. Due to the large difference in atomic size between V and Ta elements and elements such as Ni, Co, and Cr, severe lattice distortion can be caused, which can significantly increase the lattice resistance of the matrix and achieve a better solid solution strengthening effect. At the same time, vanadium can also increase the lattice resistance of L12 phase-strengthened medium-entropy alloy, thereby improving the ultra-low temperature mechanical strength. However, excessive addition of vanadium will inhibit the occurrence of deformation twins and damage the toughness to a certain extent. Adding tantalum to the alloy to replace part of the vanadium can reduce the inhibitory effect of vanadium on deformation twins, while increasing the lattice resistance of the medium-entropy alloy, thereby improving the ultra-low temperature mechanical strength. In addition, although the simultaneous addition of tantalum and vanadium makes the composition of the medium-entropy alloy more complex, no brittle phase precipitation still occurs.
[0013] (3) Fine-grained structures can be obtained through cold rolling and aging heat treatment, thereby fully utilizing the grain refinement strengthening effect to improve the mechanical strength of medium-entropy alloys; a large number of annealing twins also exist in the structure, which can play a "dynamic grain refinement strengthening" role, further enhancing the mechanical strength of medium-entropy alloys. In addition, during solution heat treatment or aging heat treatment, partial recrystallization of alloy grains produces heterogeneous grain structures, which can also produce back stress strengthening effects; high-density dislocations in unrecrystallized grains provide excellent dislocation strengthening effects, and small-sized recrystallized grains produce excellent grain refinement strengthening effects.
[0014] Preferably, the solution heat treatment temperature is 1050-1200℃, and the solution heat treatment time is 8-12h.
[0015] Preferably, the (NiCoCr) 73 The thickness of the V2Ta(Ni6AlTi)3 alloy ingot is 10-20mm. In the cold rolling deformation, the amount of reduction each time is 4-6% of the original thickness of the alloy, until the final thickness of the alloy is reduced by 70-90% compared with the original thickness of the alloy.
[0016] Preferably, the aging heat treatment temperature is 700-900℃, and the aging heat treatment time is 20-30h.
[0017] Preferably, the vacuum melting is magnetic levitation induction melting, the voltage of the magnetic levitation induction melting is 500-600V, the current of the magnetic levitation induction melting is 400-500A, the number of vacuum meltings is 2-4, and the time of each vacuum melting is 15-25min.
[0018] Preferably, the medium-entropy alloy contains nano-L12 precipitates, the average particle size of which is 9-75 nm and the volume percentage is 10-30%.
[0019] Preferably, the medium-entropy alloy has a face-centered cubic crystal structure, and the average grain size of the medium-entropy alloy is 2-5 μm.
[0020] Preferably, the medium-entropy alloy has a yield strength of 1500-2200 MPa, a tensile strength of 2000-2500 MPa, and a fracture strain of 7-30% at 4.2 K.
[0021] The medium-entropy alloy of the present invention contains nano-L12 precipitates and does not contain other brittle phases, thereby achieving the goal of simultaneously increasing the strength and toughness of the medium-entropy alloy at ultra-low temperatures.
[0022] Compared with the prior art, the present invention has the following beneficial effects: By selecting specific alloying elements and cooperating with corresponding solution heat treatment, cold rolling deformation, and aging heat treatment, the present invention can give full play to the effects of lattice strengthening, solution strengthening, precipitation strengthening, and grain refinement strengthening, as well as the back stress strengthening effect generated by heterogeneous grain structure, so as to simultaneously increase the strength and toughness of medium-entropy alloys at ultra-low temperatures, and can meet the requirements of key components of high-end cryogenic equipment for ultra-low temperature high strength and toughness materials. Detailed Implementation
[0023] To better illustrate the purpose, technical solution, and advantages of this invention, specific embodiments will be used to further explain the invention below. Unless otherwise specified, the test methods used in the embodiments and / or comparative examples are conventional methods; the materials and reagents used, unless otherwise specified, are commercially available.
[0024] Example 1
[0025] A method for preparing a medium-entropy alloy includes the following steps:
[0026] (1) The elemental metal raw materials of Co, Cr, Ni, Al, Ti, V, and Ta are cleaned sequentially by acid washing, ultrasonic alcohol cleaning, and vacuum drying. (NiCoCr) 73 The atomic percentages of V₂Ta(Ni₆AlTi)₃ were converted to mass, and the cleaned elemental metals of Co, Cr, Ni, Al, Ti, V, and Ta were accurately weighed to an accuracy of 0.1 mg. All the metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting, with the voltage controlled at 550V and the current at 450A. Melting was performed three times, each time for 20 minutes. After melting, the molten alloy was cast into a copper mold and cooled to obtain a medium-entropy alloy (NiCoCr). 73 V2Ta(Ni6AlTi)3 ingot;
[0027] (2) (NiCoCr) 73V2Ta(Ni6AlTi)3 ingots were subjected to solution heat treatment at 1150℃, held at this temperature for 10 hours, and then quenched and cooled in water.
[0028] (3) After cold rolling deformation, the initial thickness of the alloy is 10-20mm. The amount of rolling roll reduction is 5% of the initial thickness until the final thickness is reduced by 80%.
[0029] (4) After aging heat treatment at 700℃ for 24h and water quenching, the grain size of the medium-entropy alloy is about 2 micrometers. In addition, there is a high density of nano-L12 precipitates (about 9nm, content 27%). The resulting medium-entropy alloy has a yield strength of 2165MPa, a tensile strength of 2427MPa and a fracture strain of about 7.3% at 4.2K.
[0030] Example 2
[0031] A method for preparing a medium-entropy alloy includes the following steps:
[0032] (1) The elemental metal raw materials of Co, Cr, Ni, Al, Ti, V, and Ta are cleaned sequentially by acid washing, ultrasonic alcohol cleaning, and vacuum drying. (NiCoCr) 73 The atomic percentages of V₂Ta(Ni₆AlTi)₃ were converted to mass, and the cleaned elemental metals of Co, Cr, Ni, Al, Ti, V, and Ta were accurately weighed to an accuracy of 0.1 mg. All the metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting, with the voltage controlled at 550V and the current at 450A. Melting was performed three times, each time for 20 minutes. After melting, the molten alloy was cast into a copper mold and cooled to obtain a medium-entropy alloy (NiCoCr). 73 V2Ta(Ni6AlTi)3 ingot;
[0033] (2) (NiCoCr) 73 V2Ta(Ni6AlTi)3 ingots were subjected to solution heat treatment at 1150℃, held at this temperature for 10 hours, and then quenched and cooled in water.
[0034] (3) After cold rolling deformation, the initial thickness of the alloy is 10-20mm. The amount of rolling roll reduction is 5% of the initial thickness until the final thickness is reduced by 80%.
[0035] (3) After aging heat treatment at 800℃ for 24h and water quenching, the grain size of the medium-entropy alloy is about 3 micrometers. In addition, there is a high density of nano-L12 precipitates (about 30nm, content 19%). The resulting medium-entropy alloy has a yield strength of 1967MPa, a tensile strength of 2255MPa and a fracture strain of about 11.0% at 4.2K.
[0036] Example 3
[0037] A method for preparing a medium-entropy alloy includes the following steps:
[0038] (1) The elemental metal raw materials of Co, Cr, Ni, Al, Ti, V, and Ta are cleaned sequentially by acid washing, ultrasonic alcohol cleaning, and vacuum drying. (NiCoCr) 73 The atomic percentages of V₂Ta(Ni₆AlTi)₃ were converted to mass, and the cleaned elemental metals of Co, Cr, Ni, Al, Ti, V, and Ta were accurately weighed to an accuracy of 0.1 mg. All the metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting, with the voltage controlled at 550V and the current at 450A. Melting was performed three times, each time for 20 minutes. After melting, the molten alloy was cast into a copper mold and cooled to obtain a medium-entropy alloy (NiCoCr). 73 V2Ta(Ni6AlTi)3 ingot.
[0039] (2) (NiCoCr) 73 V2Ta(Ni6AlTi)3 ingots were subjected to solution heat treatment at 1150℃, held at this temperature for 10 hours, and then quenched and cooled in water.
[0040] (3) After cold rolling deformation, the initial thickness of the alloy is 10-20mm. The amount of rolling roll reduction is 5% of the initial thickness until the final thickness is reduced by 80%.
[0041] (4) After aging heat treatment at 900℃ for 24h and water quenching, the grain size of the medium-entropy alloy is about 5 micrometers. In addition, there is a high density of nano-L12 precipitates (about 75nm, content 12%). The resulting medium-entropy alloy has a yield strength of 1523MPa, a tensile strength of 2020MPa and a fracture strain of about 26.1% at 4.2K.
[0042] Comparative Example 1
[0043] A method for preparing a medium-entropy alloy includes the following steps:
[0044] (1) The elemental metal raw materials of Co, Cr, Ni, Al, Ti, V, and Ta are cleaned sequentially by acid washing, ultrasonic alcohol cleaning, and vacuum drying. (NiCoCr) 73The atomic percentages of V₂Ta(Ni₆AlTi)₃ were converted to mass, and the cleaned elemental metals of Co, Cr, Ni, Al, Ti, V, and Ta were accurately weighed to an accuracy of 0.1 mg. All the metal raw materials were placed in a magnetic levitation induction melting furnace for vacuum melting, with the voltage controlled at 550V and the current at 450A. Melting was performed three times, each time for 20 minutes. After melting, the molten alloy was cast into a copper mold and cooled to obtain a medium-entropy alloy (NiCoCr). 73 V2Ta(Ni6AlTi)3 ingot.
[0045] (2) (NiCoCr) 73 V2Ta(Ni6AlTi)3 ingots were subjected to solution heat treatment at 1150℃, held at this temperature for 10 hours, and then quenched and cooled in water.
[0046] (3) After cold rolling deformation, the initial thickness of the alloy is 10-20mm. The amount of rolling roll reduction is 5% of the initial thickness until the final thickness is reduced by 80%.
[0047] (3) After aging heat treatment at 1100℃ for 24h and water quenching, the grain size of the medium-entropy alloy is about 200 micrometers. There are no nano-L12 precipitates. It is a single-phase supersaturated solid solution structure. The yield strength of the obtained medium-entropy alloy at 4.2K is 801MPa, the tensile strength is 1355MPa, and the fracture strain is about 52.4%.
[0048] The yield strength, tensile strength, and fracture strain of the medium-entropy alloy prepared above were tested at 4.2K, and the test results are shown in Table 1. Before conducting the 4.2K test, a rod-shaped tensile specimen was prepared with a gauge length of 22 mm and a gauge diameter of 4 mm. The tensile rate during the test was 5 × 10⁻⁶. -4 / s, the sample is stretched in liquid helium, and the strain of the alloy is measured using an extensometer.
[0049] Table 1
[0050]
[0051] As can be seen from the above embodiments, the medium-entropy alloy of the present invention has a yield strength of 1500-2200MPa, a tensile strength of 2000-2500MPa, and a fracture strain of 7-30% at 4.2K, exhibiting excellent strength and toughness at ultra-low temperatures.
[0052] As can be seen from Examples 1-3 and Comparative Example 1, the aging heat treatment temperature affects the mechanical properties of the medium-entropy alloy. In Examples 1-3, the aging heat treatment at 700-900℃ resulted in partial recrystallization, and nano-L12 phase precipitated in the microstructure. There were no other brittle phases, and the content and size of the nano-L12 precipitate changed with the aging temperature. The average particle size of the nano-L12 precipitate was 9-75nm, and the volume percentage was 10-30%. The aging temperature had a significant effect on the grain size, and the average grain size of the medium-entropy alloy was 2-5μm, resulting in the final alloy having better strength and toughness at ultra-low temperatures. In Comparative Example 1, the aging heat treatment at 1100℃ resulted in complete recrystallization in the alloy, and there were no nano-L12 precipitates in the microstructure. The microstructure was a single-phase supersaturated solid solution. Although the toughness at ultra-low temperatures was excellent, the strength was low.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A medium-entropy alloy, characterized in that, The chemical formula of the medium-entropy alloy is (NiCoCr). 73 V2Ta(Ni6AlTi)3, the medium-entropy alloy contains nano-L12 precipitates with an average particle size of 9-75 nm and a volume percentage of 10%-30%. The average grain size of the medium-entropy alloy is 2-5 μm. The medium-entropy alloy has a yield strength of 1500-2200 MPa, a tensile strength of 2000-2500 MPa, and a fracture strain of 7%-30% at 4.2 K. The preparation method of the medium-entropy alloy includes the following steps: (1) Clean the raw materials of elemental metals Co, Cr, Ni, Al, Ti, V and Ta respectively, and then make them according to the chemical formula (NiCoCr) based on the percentage of metal atoms. 73 V2Ta(Ni6AlTi)3 is prepared by weighing the various elemental metals and performing vacuum melting. After melting, the molten alloy is cast to obtain (NiCoCr). 73 V2Ta(Ni6AlTi)3 alloy ingot; (2) (NiCoCr) 73 The V2Ta(Ni6AlTi)3 alloy ingot is subjected to solution heat treatment, cold rolling deformation, and aging heat treatment in sequence to obtain the medium entropy alloy; the aging heat treatment temperature is 700-1000℃; and the solution heat treatment time is 8-12h.
2. The medium-entropy alloy as described in claim 1, characterized in that, The solution heat treatment temperature is 1050-1200℃.
3. The medium-entropy alloy as described in claim 1, characterized in that, The (NiCoCr) 73 The thickness of the V2Ta(Ni6AlTi)3 alloy ingot is 10-20mm. In the cold rolling deformation, the amount of reduction each time is 4-6% of the original thickness of the alloy, until the final thickness of the alloy is reduced by 70-90% compared with the original thickness of the alloy.
4. The medium-entropy alloy as described in claim 1, characterized in that, The aging heat treatment time is 20-30 hours.
5. The medium-entropy alloy as described in claim 1, characterized in that, The vacuum melting is magnetic levitation induction melting, the voltage of the magnetic levitation induction melting is 500-600V, the current of the magnetic levitation induction melting is 400-500A, the number of vacuum meltings is 2-4, and the time of each vacuum melting is 15-25min.
6. The medium-entropy alloy as described in claim 1, characterized in that, The medium-entropy alloy has a face-centered cubic crystal structure.
Citation Information
Patent Citations
Medium-entropy alloy and preparation method thereof
CN115927944A
